DECONSTRUCTING NIGERIA’S DATA PROTECTION REGIME FROM CONSUMER PROTECTION PERSPECTIVE - Okechukwu Ukwueze, Festus; Ibegbulem, Justin (Law, State and Telecommunications Review, 2021)
Purpose – The purpose of this paper is to make a case for the recognition of privacy and personal data protection as species of consumer rights in Nigeria in line with the revised United Nations Guidelines for Consumer Protection (UNGCP) by amending existing laws or enacting a new law to provide for personal data protection regime for consumers. Methodology/Approach/Design – The study follows a structured review of relevant extant legislation on consumer protection and personal data protection, namely the Federal Competition and Consumer Protection Act 2018 (FCCPA) and the Nigeria Data Protection Regulation 2019 (NDPR). Findings – The paper identifies that the provisions of Nigeria’s foremost consumer protection legislation, FCCPA, does cover electronic commerce (e-commerce) or consumer privacy and personal data protection while the NDPR, subsidiary legislation on personal data protection, which is yet to be effectively implemented is too general as to provide the consumers the much-needed privacy protection in their dealings with businesses. Practical Implications–Given the importance Recognition of data privacy and personal data protection as a species of consumer rights helps in understanding consumer protection in online transactions and opens opportunities for future research on consumer privacy and data protection. Originality/Value – Given the importance attached to the protection of consumer privacy and the various ramifications of transactions involving exposure of consumers’ personal data, recognition of privacy consumers’ rights to privacy is vital in consolidating knowledge of consumer rights and identifying paths for future research.